Caregivers' Experience with Lip Taping as a Presurgical Orthopedic Treatment for Cleft Lip and Palate Defects - Athar Thair; Mushriq Abid; Arkadiusz Dziedzic (MDPI AG, 2024)
Background: This study aimed to assess caregivers' experiences and perceptions of applying lip taping as presurgical orthopedic therapy (PSO) for infants with a cleft lip and palate. Methods: A retrospective survey was conducted, inviting parents to respond to a series of structured questions between September 2022 and June 2023. The questionnaire focused on evaluating parents' experience with lip taping, a crucial component of PSO. Descriptive statistics and the Chi-square test were employed to analyze relationships between categorical variables. Results: Of the 157 participants, overall, 122 completed the survey, forming the dataset for analysis. A majority (90.0%) reported sufficient experience in using lip taping and no major difficulties with lip taping application. Caregivers with higher education levels exhibited a significantly positive correlation (p = 0.015). Additionally, 93.4% confirmed the efficacy of lip taping for premaxillary segment retraction, with this outcome being correlated with caregivers' knowledge and education (p = 0.008). Interestingly, caregivers' age also demonstrated a substantial association (p = 0.020). Conclusions: While a vast majority expressed positive experiences with lip taping as a presurgical treatment, continuous, tailored education on cleft lip and palate is imperative. This education should be directed towards caregivers and individuals offering direct support to parents of children with CLP, ensuring optimal care and preparation for surgical treatment.